The Wealth of Nations: a tradition-historical study - Chan, Michael J. (Forschungen zum Alten Testament, 2017)
Cover -- Preface -- Table of Contents -- List of Abbreviations -- Chapter 1: Tradition History and Art History: Toward a Synthesis -- A. Creatio ex Traditione -- B. Tradition and Society -- C. Tradition History (Traditionsgeschichte) and Transmission History (Überlieferungsgeschichte) -- D. Iconography and Tradition History -- E. Putting Theory into Practice: The Wealth of Nations Tradition -- Chapter 2: The Wealth of Nations Tradition in the Hebrew Bible -- A. Defining the Body of Textual Evidence -- B. Poetry, Colometry, and Compositional History -- C. A Linguistic, Generic, and Diachronic Profile of the Biblical Texts -- I. 1 Kgs 10:1-10, 13//2 Chr 9:1-9, 12 -- 1. Contents and Genre -- 2. Compositional History -- II. 1 Kgs 10:15//2 Chr 9:14 -- 1. Contents and Genre -- 2. Compositional History -- III. 1 Kgs 10:23-25//2 Chr 9:22-24 -- 1. Contents and Genre -- 2. Compositional History -- IV. 2 Chr 32:23 -- 1. Contents and Genre -- 2. Compositional History -- V. Isa 18:7 -- 1. Contents and Genre -- 2. Compositional History -- VI. Isa 45:14 -- 1. Contents and Genre -- 2. Compositional History -- VII. Isa 60:4-17 -- 61:5-6 -- 1. Contents and Genre -- 2. Compositional History -- VIII. Isa 66:12 -- 1. Contents and Genre -- 2. Compositional History -- IX. Zeph 3:10 -- 1. Contents and Genre -- 2. Compositional History -- X. Ps 68:19a, 29-32 -- 1. Contents and Genre -- 2. Compositional History -- XI. Ps 72:10-11 -- 1. Contents and Genre -- 2. Compositional History -- XII. Ps 76:12 -- 1. Contents and Genre -- 2. Compositional History -- XIII. Ps 96:7-8//1 Chr 16:28-29 -- 1. Contents and Genre -- 2. Compositional History -- D. A Tabular Presentation of all Linguistic, Generic, and Diachronic Evidence from Chapters 3-4 -- I. Wealth Bearers -- II. The Terminology of Foreign Wealth -- III. The Terminology of Wealth-Bearing.